Topology optimization methods for tower structural designs involving fluid-structure interaction and soil-structure interaction. - Silva, Kamilla Emily Santos (2023)
This work aims to develop and apply topology optimization methodologies for optimized designs of tower-like structures involving two important classes of Multiphysics problems: Fluid- Structure Interaction (FSI) and Soil-Structure Interaction (SSI). The analysis and modeling of problems involving more than one physical phenomenon is a potentially challenging topic in the topology optimization (TO) framework. The strong coupling between the physical domains which, in some cases, entails the constant change of structural loads in terms of location, direction and magnitude or the presence of more than one type of material in the same domain are challenges present in this type of problem. In this work, two methodologies based on a binary method are developed in order to design structures with well-defined boundaries and mitigate the main difficulties encountered in the application of topology optimization in multiphysics systems. The Topology Optimization of Binary Structures (TOBS) method, which is based on integer linear programming and employs binary variables {0,1}, is used as the base formulation in order to find optimized fluid-structure and soil-structure layouts. In the FSI class of problems, 3D numerical examples are solved and large displacements are included. In the SSI systems, static and dynamic loads are considered. To the best of authors knowledge, this is the first work to employ binary topology optimization in FSI design including large displacements and strictly binary variables into the design of SSI systems. Numerical problems are solved and the the advantages of each methodology are particularly pointed out in each chapter.